An investigation into the use of spreadsheet algebra programmes (SAPS) to influence teacher change in selected township high schools - Dumisani Emmanuel, Mdlalose (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEd)--Stellenbosch University, 2017